2023
DOI: 10.3390/w15152796
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Zooplankton Community and Water Quality in an Artificial Freshwater Lake from a Semi-Arid Area (Irbid, Jordan)

Abstract: Zooplankton play a crucial role in aquatic food chains and contain many species, which could be bioindicators of water quality and ecosystem health. The ecological impacts of eutrophication on zooplankton composition in freshwater lakes have recently gained wide interest. Geographic location and water-body size influence zooplankton diversity in freshwaters; meanwhile, less is known about the composition and dynamic of the zooplankton community and their relationship with the trophic status in artificial water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Higher phosphorus (TP) concentrations observed in Sri Serdang Pond (0.69 ± 0.10 mg L −1 ) and Cempaka Lake (0.52 ± 0.02 mg L −1 ) were presumably due to the wastewater discharge from nearby restaurants, stalls, and settlements. Previous studies have also reported that nutrients were the main factors affecting the spatial differentiation pattern of zooplankton [17,42,[66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Higher phosphorus (TP) concentrations observed in Sri Serdang Pond (0.69 ± 0.10 mg L −1 ) and Cempaka Lake (0.52 ± 0.02 mg L −1 ) were presumably due to the wastewater discharge from nearby restaurants, stalls, and settlements. Previous studies have also reported that nutrients were the main factors affecting the spatial differentiation pattern of zooplankton [17,42,[66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%